Effect of a Multifaceted Approach on Perceived Support Among Mothers of Preterm Infants: A Quasi-Experimental Study - Parisa Mohagheghi; Fatemeh Razavinia PhD; Ahmad Khosravi PhD; Seyedeh Saeedeh Mousavi PhD (SAGE Publishing, 2024)
Introduction Mothers of preterm infants need support to deal with the issues caused by the early birth of their infants. Objective The authors examined the impact of a multifaceted supportive approach on the mothers' perceived support levels. Methods The present quasi-experimental study was performed on 143 mother-preterm infant pairs, in two neonatal intensive care units (NICUs) of referral and educational hospitals in Tehran, Iran. The base of developed interventions was known to support system patterns of mothers with preterm infants. Different supportive interventions (appraisal, instrumental, emotional, and informational) of mothers were implemented during three months. The Nurse Parent Support Tool was applied for assessing perceptions of perceived support by mothers. Routine care was provided for the control group. The results were analyzed by STATA software 13. Categorical variables were analyzed by chi-square test, t -test, and inverse probability treatment weights. Results Following adjustments of mean differences of outcomes between study groups (95% confidence interval), all support scores, such as instrumental support, −1.23 (95% CI −1.04 to −1.43), total support, −1.83 (95% CI −1.6 to −2.06), appraisal support, −2.01 (95% CI −1.73 to −2.29), emotional support, −1.87 (95% CI −2.15 to 1.6), and informational support, −2.12 (95% CI −1.82 to −2.43), were significantly higher in the interventional group than in the control group ( p  < .001). Conclusions Support received by mothers of preterm infants determines maternal/neonatal health. Information sharing and effective ways to support are essential elements in the mother's ability to deal with the new, stressful situation. This multifaceted supportive approach considerably improved mothers' perceived support.